Perbandingan Kinerja Bank Pembiayaan Rakyat Syariah dan Bank Perkreditan Rakyat di Indonesia - Aliefah, Aniesatun Nurul; Renfiana, Lilis (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
The purpose of this study is to compare the performance of The Conventional Rural Bank (BPR) and Islamic Rural Bank (BPRS) in Indonesia using the REC method which consists of a risk profile, earnings, and capital during the 2015-2017 period. The risk profile factor is represented by the NPF indicator, income is represented by ROA and capital is represented by CAR. By using the purposive sampling method, as many as 43 Islamic Rural Bank (BPRS) and 63 Conventional Rural Bank (BPR) were obtained from secondary data sourced from annual financial reports published on the bank's official website. The analysis technique was then carried out using the Mann-Whitney-U test to compare the performance of the two banks. The results of this study indicate that there is a significant difference in NPF between the two banks at a significance level of 0.006; There is no significant difference in ROA and CAR between Islamic general financing banks and rural credit banks in Indonesia at the ROA significance level of 0.070 and CAR 0.239, respectively. The implication of this research implies that the performance of Islamic BPRs still has a great opportunity to develop in the future and is a big challenge, especially for the management of Indonesian Islamic BPRs and the central bank (Bank Indonesia) as a bank. regulators.